ADHD medications and cardiovascular adverse events in children and adolescents: cross‐national comparison of risk communication in drug labeling. Issue 3 (13th January 2017) - Sieluk, Jan; Palasik, Brittany; dosReis, Susan; Doshi, Peter
Abstract: Purpose: Regulators approve written medical information for healthcare professionals and consumers, but the consistency of these sources has not been studied. We investigated the consistency of information regarding four cardiovascular risks of attention‐deficit/hyperactivity disorder (ADHD) medications approved in four countries. Methods: Professional and consumer product labeling for five ADHD medications approved in Australia, Canada, the UK, and the USA were obtained in March/April 2016. Language describing the relationship between medication and elevated blood pressure and/or heart rate, myocardial infarction, stroke, and sudden death was extracted verbatim and classified into one of four categories based on the described relationship between medication and adverse event: "confirmed, " "unconfirmed, " "mixed, " and "not mentioned." We judged the consistency of messages delivered to healthcare professionals and consumers as either "consistent" or "inconsistent." Results: We obtained 20 healthcare professional labels and 20 corresponding consumer labels for the five ADHD medications registered in all four countries. Not all professional and consumer labeling contained language regarding all four adverse events. Of the 80 theoretically evaluable drug‐risk pairs, 38 (48%) were not evaluable because of absence of mention of the adverse event in the consumer label. For the remaining 42, the potential causal relationship was expressed consistently in professional and consumer labeling in 25 (60%) cases. The cardiovascular risk profile was not described consistently across all four countries for any of the five drugs. Conclusions: Product labeling provides healthcare professionals and consumers with inconsistent messages regarding the potential causal relationship between stimulant use and specific cardiovascular risks in children and adolescents. Copyright © 2017 John Wiley & Sons, Ltd.